A Case Report of Adrenocorticotropic Hormone to Treat Recurrent Focal Segmental Glomerular Sclerosis Post-Transplantation and Biomarker Monitoring - Anwar, Siddiq; Larson, Derek S.; Naimi, Nima; Ashraf, Muhammad; Culiberk, Nancy; Liapis, Helen; Wei, Changli; Reiser, Jochen; Brennan, Daniel C. (Frontiers in Medicine, 2015)
Background: Recurrent focal segmental glomerular sclerosis (rFSGS) in renal transplant recipients (RTR) is difficult to predict and treat. Early rFSGS is likely from circulating factors and preformed antibodies. Methods: We present the case of a 23-year-old white man who presented with rFSGS and acute renal failure requiring dialysis 9-months after a 1-haplotype matched living-related transplant. We retrospectively analyzed serum samples from various clinical stages for rFSGS biomarkers: serum glomerular albumin permeability (Palb), soluble urokinase-type plasminogen activator receptor (suPAR) serum level with suPAR-β3 integrin signaling on human podocytes, and angiotensin II type I receptor-antibody (AT1R-Ab) titer. Results: All biomarkers were abnormal at 1-year pre-transplant prior to initiation of dialysis and at the time of transplant. After initiation of hemodialysis, β3 integrin activity on human podocytes, in response to patient serum, as well as AT1R-Ab were further elevated. At the time of biopsy-proven recurrence, all biomarkers were abnormally high. One week after therapy with aborted plasmapheresis (secondary to intolerance), and high dose steroids, the Palb and suPAR- β3 integrin activity remained significantly positive. After 12-weeks of treatment with high-dose steroids, rituximab, and galactose, the patient remained hemodialysis-dependent. Three-months after his initial presentation we commenced adrenocorticotropic hormone (ACTH, Acthar® Gel), 80 units subcutaneously twice weekly. Four-weeks later he was able to discontinue dialysis. After 8-months of maintenance ACTH therapy, his serum creatinine stabilized at 1.79 mg/dL with less than 1 gram of proteinuria. Conclusion: ACTH therapy was associated with improvement in renal function within 4 weeks. The use of rFSGS biomarkers may aid in predicting development of rFSGS.